Chemical constituents from the fruiting bodies of Amauroderma subresinosum. Issue 11 (1st November 2016) - Wang, Qiao; Wang, Yu-Guang; Ma, Qing-Yun; Huang, Sheng-Zhuo; Kong, Fan-Dong; Zhou, Li-Man; Dai, Hao-Fu; Zhao, You-Xing
Abstract: The chemical investigation on the fruiting bodies of Amauroderma subresinosum led to the isolation of 10 compounds including 2 new ones named amaurosubresin (1 ) and erythro (23, 24)-5α, 6α-epoxyergosta-8-ene-7-one-3β, 23-diol (2 ). Their structures were elucidated on the basis of 1D and 2D NMR spectroscopy as well as MS. The bioassay of inhibitory activity against acetylcholinesterase (AChE) of two new isolates exhibited definite inhibitory activity.